2019
DOI: 10.2174/1381612824666181003113444
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical-based Integrative Medicine: Adopting a Mediterranean Diet Pyramid for Attaining Healthy Ageing in Veterans with Disabilities

Abstract: Veterans with disability represent a big burden worldwide and often require long-term rehabilitation. Unhealthy dietary and lifestyle habits, including smoke and alcohol abuse, are common in veterans. In the context of integrative medicine approaches, the "complementary and alternative medicine" has been suggested for the management of chronic diseases. However, the potential risk of interaction between herbal products, dietary supplements and drugs must be considered in veterans. The Mediterranean diet has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 199 publications
(245 reference statements)
0
13
0
Order By: Relevance
“…A systematic review of dietary interventions in adults with SCI emphasized the potential of diet in conjunction with exercise in minimizing CVD risk [69] , whereas the "Consortium for Spinal Cord Medicine" noted success in weight loss using the Med-D in the DPP [63] . Med-D has been suggested for Veterans with disabilities [70] , patients with chronic kidney disease (CKD) [71] and individuals with chronic pain [72] . Furthermore, Allison et al [73] , recently reported that in individuals with SCI, a 3-mo anti-inflammatory diet similar to the Med-D plus supplementation decreased fat intake and proinflammatory dietary components (trans fatty acids, caffeine and sodium) and increased protein intake and some nutrients with established anti-inflammatory properties, including vitamins A, C, and E, and omega (ω)-3 polyunsaturated fatty acids (PUFA), with no change in CHO or energy intake [73] .…”
Section: Dietary Advice and Mediterranean Diet-based Pyramid For Indimentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review of dietary interventions in adults with SCI emphasized the potential of diet in conjunction with exercise in minimizing CVD risk [69] , whereas the "Consortium for Spinal Cord Medicine" noted success in weight loss using the Med-D in the DPP [63] . Med-D has been suggested for Veterans with disabilities [70] , patients with chronic kidney disease (CKD) [71] and individuals with chronic pain [72] . Furthermore, Allison et al [73] , recently reported that in individuals with SCI, a 3-mo anti-inflammatory diet similar to the Med-D plus supplementation decreased fat intake and proinflammatory dietary components (trans fatty acids, caffeine and sodium) and increased protein intake and some nutrients with established anti-inflammatory properties, including vitamins A, C, and E, and omega (ω)-3 polyunsaturated fatty acids (PUFA), with no change in CHO or energy intake [73] .…”
Section: Dietary Advice and Mediterranean Diet-based Pyramid For Indimentioning
confidence: 99%
“…A systematic review emphasized the potential of diet in conjunction with exercise in minimizing CVD risk in SCI [69] , whereas the Consortium for Spinal Cord Medicine did not recommend a single nutritional intervention but noted success in weight loss using the Med-D in the DPP [63] . Med-D has been suggested for Veterans with disability [70] , patients with CKD [71] and individuals with chronic pain [72] .…”
Section: Dietary Advice and Mediterranean Diet-based Pyramid For Indimentioning
confidence: 99%
See 3 more Smart Citations